2008
DOI: 10.2320/matertrans.me200717
|View full text |Cite
|
Sign up to set email alerts
|

A Portrait of Copper Processed by Equal Channel Angular Pressing

Abstract: Copper is one of the most important materials used for electrical connectors with a high thermal and electricial conductivity, and there is an ongoing demand to improve its mechanical properties without sacrificing other beneficial properties. A possible approach to achieving this aim is to use the method of severe plastic deformation to obtain an ultrafine grained microstructure. Significant grain refinement obtained by equal channel angular pressing (ECAP) leads to an improvement of mechanical, microstructur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 14 publications
2
18
0
Order By: Relevance
“…Several papers reported a hardness peak in pure Cu processed by HPT [20,21] and ECAP [22][23][24], whereas the hardness peak for Cu was not reported in several other papers using HPT [25][26][27][28] and ECAP [29][30][31][32]. The current authors showed that Cu exhibits a hardness behavior similar to Al after HPT at a homologous temperature corresponding to room temperature of Al and successively keeping the samples at the same homologous temperature after HPT [33].…”
Section: Introductionmentioning
confidence: 53%
“…Several papers reported a hardness peak in pure Cu processed by HPT [20,21] and ECAP [22][23][24], whereas the hardness peak for Cu was not reported in several other papers using HPT [25][26][27][28] and ECAP [29][30][31][32]. The current authors showed that Cu exhibits a hardness behavior similar to Al after HPT at a homologous temperature corresponding to room temperature of Al and successively keeping the samples at the same homologous temperature after HPT [33].…”
Section: Introductionmentioning
confidence: 53%
“…A) As the most simple structure, a various kind of pure metals of high and commercial purity such as aluminum, [87][88][89][90][91][92][93][94] copper, 6,37,[95][96][97][98][99][100][101][102][103][104][105][106] iron, 76,107) titanium, [108][109][110][111][112][113][114] magnesium, 34,72,[115][116][117] have been processed by SPD for corrosion studies. In this simple system, grain size or grain boundary density impacts the corrosion resistance as a primary metallurgical variable with very few other metallurgical changes involved.…”
Section: Pure Metals With High and Commercial Purity (Typementioning
confidence: 99%
“…Corrosion behavior has been investigated on UFG materials fabricated mainly by processing of SPD such as ECAP, ARB, HPT for aluminum and its alloy, [87][88][89][90][91][92][93]120,121,143,[150][151][152][153]156,[158][159][160][161][162][163][164][165][166][167][168][169][170][171] magnesium and its alloy, 34,72,[115][116][117]122,123,154,157,[172][173][174][175][176][177][178][179] copper and its alloy, 6,[96][97][98]…”
Section: General Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…They observed a rather smooth surface with a smaller penetration rate at grain boundaries and thus considerable improvement in intergranular corrosion. For SPD materials, corrosion behavior such as general [10][11][12][13][14][15][16][17][18][19][20], intergranular [21][22][23] and pitting corrosion [21,[24][25][26][27][28][29][30][31][32] of UFG aluminum and aluminum alloy [17,21,22,24,25,[29][30][31][32], copper and copper alloy [11,15,19,28] as well as stainless steels [10,12,18,23,27] and magnesium [13,14,16,20] processed by SPD, and corrosive environment dependence [33][34]…”
Section: Introductionmentioning
confidence: 99%